2019
DOI: 10.1021/acs.jpcb.9b00518
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Oxygenase-Pathway Reactions Catalyzed by Rubisco from Large-Scale Kohn–Sham Density Functional Calculations

Abstract: Ribulose 1,5-bisphosphate carboxylase-oxygenase (Rubisco) is the primary carbon-fixing enzyme in photosynthesis, fixing CO2 to a 5-carbon sugar, RuBP, in a series of five reactions. However, it also catalyzes an oxygenase reaction by O2 addition to the same enolized RuBP substrate in an analogous reaction series in the same active site, producing a waste product and loss of photosynthetic efficiency. Starting from RuBP, the reactions are enolization to the enediolate form, addition of CO2 or O2 to form the car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…It is possible that both binding and dissociation are feasible by flipping between singlet and triplet states where the energy surfaces crossover (intersystem crossing). This has been verified by our quantum chemical calculations (Kannappan et al, 2019). Note that this is the first study in the literature that has addressed directly how the formally spin-forbidden oxygenation step (triplet O 2 to singlet peroxo adduct) can be achieved.…”
Section: Experimental Evidence Against Decarboxylation and Deoxygenationsupporting
confidence: 83%
See 1 more Smart Citation
“…It is possible that both binding and dissociation are feasible by flipping between singlet and triplet states where the energy surfaces crossover (intersystem crossing). This has been verified by our quantum chemical calculations (Kannappan et al, 2019). Note that this is the first study in the literature that has addressed directly how the formally spin-forbidden oxygenation step (triplet O 2 to singlet peroxo adduct) can be achieved.…”
Section: Experimental Evidence Against Decarboxylation and Deoxygenationsupporting
confidence: 83%
“…Point 1: Our recent computational study (Kannappan et al, 2019) suggests that rates of catalysis and deoxygenation may well be very similar. The overall reaction, i.e., to products, is certainly highly exothermic, so it clearly cannot be reversed.…”
Section: Experimental Evidence Against Decarboxylation and Deoxygenationmentioning
confidence: 99%
“…This tends to suggest some level of correlation between carboxylase and oxygenase k i , most likely with those associated with substrate affinity ( Figure 6 ). Both substrates present similar electrostatic potentials to the RuBisCO active site ( Kannappan and Gready, 2008 ), so that the binding of CO 2 to enolized RuBP induces a redistribution of charge similar to that induced by O 2 binding ( Cummins et al, 2018b ; Kannappan et al, 2019 ; Bathellier et al, 2020 ; Cummins and Gready, 2020 ) which will then interact similarly with the external (to the active site) electrostatic field, which is thought to be the primary driver in enzyme catalysis ( Warshel et al, 2006 ; Fried and Boxer, 2017 ). Moreover, evolutionary changes in this electrostatic field have been linked to RuBisCO substrate specificity ( Poudel et al, 2020 ) This electrostatic field would change slightly with sequence variation outside the highly conserved active site to produce the small free energy changes required to maintain the correlation between S C and S O when mutations occur.…”
Section: Discussionmentioning
confidence: 99%
“…The combined effects of increasing population and anthropogenic climate change have motivated efforts to enhance carbon fixation in plants for increasing both agricultural crop yield and carbon sequestration generally ( Niinemets et al, 2017 ; Andralojc et al, 2018 ; Erb and Zarzycki, 2018 ; Fernie et al, 2020 ; Lawson and Flexus, 2020 ). Although the possibility of enhancing photosynthesis by improving RuBisCO kinetic traits has been given due consideration ( Whitney et al, 2011 ; Sharwood et al, 2016 ; Gomez-Fernandez et al, 2018 ; Wilson et al, 2018 ; Zhou and Whitney, 2019 ; Davidi et al, 2020 ; Lin et al, 2020 ; Bouvier et al, 2021 ), a conclusive picture of RuBisCO’s molecular mechanism ( Cleland et al, 1998 ; Tcherkez, 2013 , 2015 ; Cummins et al, 2018b , 2019b ; Kannappan et al, 2019 ; Bathellier et al, 2020 ; Cummins and Gready, 2020 ) and a general consensus understanding of the observed tradeoffs between RuBisCO’s kinetic parameters remains elusive, despite having been analyzed in varying ways with the objective of gaining insights into the possible connection between evolutionary and biochemical (or catalytic) constraints ( Bouvier et al, 2021 ). The earliest of these studies, ( Tcherkez et al, 2006 ; Savir et al, 2010 ) based on general mechanistic assumptions and limited data samples, concluded that variations in the elementary rate constants must be tightly constrained by the limitations inherent in RuBisCOs kinetic mechanism, resulting in an enzyme which provides only limited scope for further optimization ( Tcherkez et al, 2006 ; Tcherkez, 2013 , 2015 ), while later studies of more extensive data sets have challenged this view, revealing greater flexibility ( Cummins et al, 2018a , 2019a ; Flamholz et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, H 2 O 2 has been shown to be generated during oxygenation (about one molecule per 200 catalytic cycles) (18), suggesting that a reactive oxygen species might be involved in the mechanism (or that the peroxide can be broken down, yielding hydrogen peroxide). Ab initio calculations with density functional theory (DFT) using energy expression based on hybrid energy functionals B3LYP have suggested that SET is plausible, since the minimum-energy structure with bound oxygen is found to correspond to a biradical complex with partial electron transfer to O 2 (19). It has been suggested that most cofactor-less enzymes such as glucose oxidase activate O 2 by SET followed by spin transition via spin orbit coupling (SOC) (14,20), and Rubisco, perhaps, involves a similar mechanism.…”
Section: •−mentioning
confidence: 99%